-5(r+3)=-94

Simple and best practice solution for -5(r+3)=-94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(r+3)=-94 equation:


Simplifying
-5(r + 3) = -94

Reorder the terms:
-5(3 + r) = -94
(3 * -5 + r * -5) = -94
(-15 + -5r) = -94

Solving
-15 + -5r = -94

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + -5r = -94 + 15

Combine like terms: -15 + 15 = 0
0 + -5r = -94 + 15
-5r = -94 + 15

Combine like terms: -94 + 15 = -79
-5r = -79

Divide each side by '-5'.
r = 15.8

Simplifying
r = 15.8

See similar equations:

| -2x^2-x+28=0 | | s=-4.9t^2+19.6t+58.8 | | M+5=3m+9 | | 7c+7p+8= | | 2x^2+11.4x-696.51=0 | | 5(k-21)-8k=-34 | | X*2-3x=10 | | 10x-2(3x-6)=4(5x-6)-10x | | x=22+-2y | | 80=-16t^2+16t | | 80=-16t^2+32t | | 4x+6=3x+19 | | 6(-2.3x-5)+(4x+11)= | | 2x^3-13x^2-6x=0 | | -6=4z+10-7 | | 3x^2-24x-3=0 | | 80=-16t^2+32 | | 3(3-5x)-(1+7x)=3(3x+2)-5(2x-1) | | 7x+3(-7x+2)=-92 | | 2x+10+3x+50=90 | | 6.8(x-3)=-0.2x+28.6 | | -10x+18=2(9-5x) | | -6(6-7x)=342 | | .2x+2.3=3.5 | | -95-2x=67-8x | | 44-3x=7x-6 | | 80=-16t^2+128t | | 3(2x-3)-4(7-2x)=-30 | | 1-8(x-2)=57 | | (1/3)2= | | 5(3+x)+2x=8+19x | | -z=110 |

Equations solver categories